2018
DOI: 10.1039/c8cp03896a
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron spectroscopy of solvated dicarboxylate and alkali metal ion clusters, M+[O2C(CH2)2CO2]2−[H2O]n(M = Na, K;n= 1–6)

Abstract: We present results of combined experimental photoelectron spectroscopy and theoretical modeling studies of solvated dicarboxylate species (−O2C(CH2)2CO2−) in complex with Na+ and K+ metal cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Li et al recently observed the water-mediated interaction between ion and dicarboxylate which shows a similar kind of interaction between ion and glycine. 58 At 58% RH free ion solvation starts, reflected by the peak splitting. This can further be confirmed by the phenomenon of the peak position at the lowest RH for the glycine−sulfate mixtures (in Figure S12) being the same as that for fully hydrated sulfate in pure MgSO 4 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al recently observed the water-mediated interaction between ion and dicarboxylate which shows a similar kind of interaction between ion and glycine. 58 At 58% RH free ion solvation starts, reflected by the peak splitting. This can further be confirmed by the phenomenon of the peak position at the lowest RH for the glycine−sulfate mixtures (in Figure S12) being the same as that for fully hydrated sulfate in pure MgSO 4 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Mechanistically, salting-in and salting-out are rationalized in terms of ion-induced water structure breaker and maker effects . Wang et al have carried out many works on ion specificity; for example, they illustrate how kosmotrope vs chaotrope ions induce water structures, summarize the effects of organic acids in information on SOAs, describe glycine interaction with iodide, and report ion-dicarboxylate–water interactions . Ion–water interaction is important, but recent experimental evidence about the short-range structuring of water caused by ions shifted researchers’ attention toward ion–protein interaction. However, to the best of our knowledge, the report about the Hofmeister effect on the hygroscopicity of aerosols and the experimental evidence of ion–protein interactions are absent.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the solvation of salts in water is very important in the fields of physical chemistry, biochemistry, marine chemistry, and atmospheric chemistry. The interactions between salt ions and water molecules have nonnegligible effects on water hydrogen-bond networks, the solubility of different substances, and chemical reactions in aqueous solutions. Many experimental and theoretical studies have been performed to investigate the solvation processes of salts in water at the molecular level. To provide detailed information about the transition between salt contact ion pairs (CIPs) and solvent-separated ion pairs (SSIPs) with an increasing number of water molecules, in the last ten years, we investigated the structures and properties of a series of salt-water clusters using the technique of size-selected anion photoelectron spectroscopy combining with theoretical calculations. …”
Section: Introductionmentioning
confidence: 99%
“…In addition to the studies in the condensed phases, many studies were conducted in the gas phase. The structures of Ca 2+ (H 2 O) clusters were explored using infrared multiple photodissociation action spectroscopy (IRMPD) . The coordination numbers of Ca 2+ in Ca 2+ (H 2 O) n clusters were studied using threshold collision-induced dissociation (CID) and blackbody infrared radiative dissociation (BIRD) experiments combined with theoretical calculations. , Many theoretical studies have also been conducted to investigate the solvation of Ca 2+ in water. The geometric and electronic structures of calcium water complexes with one and two solvation shells were studied by means of high-level quantum calculations .…”
Section: Introductionmentioning
confidence: 99%
“…We note that a number of previous studies have been conducted to characterize the structures of isolated complexes of alkali metal cations bound to aromatic and carbonyl-containing molecules, using both IR and UV laser spectroscopy. [11][12][13][14][15][16][17][18][19][20] The interaction of an organic sunscreen such as OB with alkali metal cations is of practical interest since sunscreen mixtures include such counterions (e.g., coupled to pH buffer anions), 21 but also since they are commonly encountered in the environments where sunscreens are intensively used, including oceans and swimming pools, as well as on human skin. 22,23 2 Methods…”
Section: Introductionmentioning
confidence: 99%